2016
DOI: 10.4137/bcbcr.s41017
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Outcomes and Complications after Volume Replacement Oncoplastic Breast Conservations—The Glasgow Experience

Abstract: INTRODUCTIONOncoplastic breast conservation surgery (OBCS) combines the principles of surgical oncology and plastic surgery. OBCS has now become a growing option for the treatment of breast cancer and forms a part of breast-conserving therapy (BCT). We sought to investigate and report our experience in two breast units in Glasgow (Victoria Infirmary and Western Infirmary) on volume replacement OBCS.MATERIALS AND METHODSDetails of patients treated with volume replacement OBCS were identified from a prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 37 publications
6
25
2
1
Order By: Relevance
“…There was one local recurrence in this series at a median follow-up of 15 months. A study by Ho et al [22] has reported on oncological safety of oncoplastic breast surgery with tissue replacement techniques in 30 procedures with a follow-up of more than 4 years. In our routine practice, ICAP flaps have become the procedure of choice for reconstruction in patients undergoing BCS for tumors in the lateral or lower breast quadrants with a high tumor to breast ratio.…”
Section: Fig 3 Comparative Outcomes Across Participating Centersmentioning
confidence: 99%
“…There was one local recurrence in this series at a median follow-up of 15 months. A study by Ho et al [22] has reported on oncological safety of oncoplastic breast surgery with tissue replacement techniques in 30 procedures with a follow-up of more than 4 years. In our routine practice, ICAP flaps have become the procedure of choice for reconstruction in patients undergoing BCS for tumors in the lateral or lower breast quadrants with a high tumor to breast ratio.…”
Section: Fig 3 Comparative Outcomes Across Participating Centersmentioning
confidence: 99%
“…Current evidence is largely based on single-institution retrospective series [3][4][5][6][7][8][9][10][11][12][13][14][15] . Systematic literature reviews, meta-analyses and reviews further strengthen the evidence base but numbers in many series are small 2, [16][17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have historically reported a higher incidence of fat necrosis and flap contracture in women undergoing immediate versus delayed autologous reconstruction, with PMRT significantly exacerbating surgical morbidity. Potential support for the efficacy and tolerability of autologous tissue to radiation treatment comes from proof‐of‐principle studies evaluating chest wall microvascular perforator tissue replacement flaps (thoracodorsal artery perforator, lateral intercostal artery perforator, lateral thoracic artery perforator) after partial mastectomy and radiotherapy. The use of autologous tissue is the standard of care for delayed breast reconstruction in the irradiated patient.…”
Section: Resultsmentioning
confidence: 99%